Peak age and performance progression in world-class track-and-field athletes - Haugen, T. A.; Solberg, P. A.; Foster, C.; Morán-Navarro, R.; Breitschädel, F.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2018)
The aim of this study was to quantify peak age and improvements over the preceding years to peak age in elite athletic contestants according to athlete performance level, sex, and discipline. Individual season bests for world-ranked top 100 athletes from 2002 to 2016 (14,937 athletes and 57,049 individual results) were downloaded from the International Association of Athletics Federations` website. Individual performance trends were generated by fitting a quadratic curve separately to each athlete`s performance and age data using a linear modeling procedure. Mean peak age was typically 25-27 y, but somewhat higher for marathon and male throwers (~28-29 y). Women reached greater peak age than men in the hurdles and middle- and long-distance running events (mean difference, ±90% CL: 0.6, ±0.3 to 1.9, ±0.3 y: small to moderate). Male throwers had greater peak age than corresponding women (1.3, ±0.3 y: small). Throwers displayed the greatest performance improvements over the 5 y prior to peak age (mean [SD]: 7.0% [2.9%]), clearly ahead of jumpers, long-distance runners, hurdlers, middle-distance runners, and sprinters (3.4, ±0.2% to 5.2, ±0.2%; moderate to large). Similarly, top 10 athletes showed greater improvements than top 11-100 athletes in all events (1.0, ±0.9% to 1.8, ±1.1%; small) except throws. Women improved more than men in all events (0.4, ±0.2% to 2.9, ±0.4%) except sprints. This study provides novel insight on performance development in athletic contestants that are useful for practitioners when setting goals and evaluating strategies for achieving success.